Novel Neurostimulation-Based Haptic Feedback Platform for Grasp Interactions With Virtual Objects - Shell, Aliyah K.; Pena, Andres E.; Abbas, James J.; Jung, Ranu (Frontiers in Virtual Reality, 2022)
Haptic perception is a vital part of the human experience that enriches our engagement with the world, but the ability to provide haptic information in virtual reality (VR) environments is limited. Neurostimulation-based sensory feedback has the potential to enhance the immersive experience within VR environments by supplying relevant and intuitive haptic feedback related to interactions with virtual objects. Such feedback may contribute to an increase in the sense of presence and realism in VR and may contribute to the improvement of virtual reality simulations for future VR applications. This work developed and evaluated xTouch, a neuro-haptic platform that extends the sense of touch to virtual environments. xTouch is capable of tracking a user’s grasp and manipulation interactions with virtual objects and delivering haptic feedback based on the resulting grasp forces. Seven study participants received haptic feedback delivered via multi-channel transcutaneous electrical stimulation of the median nerve at the wrist to receive the haptic feedback. xTouch delivered different percept intensity profiles designed to emulate grasp forces during manipulation of objects of different sizes and compliance. The results of a virtual object classification task showed that the participants were able to use the active haptic feedback to discriminate the size and compliance of six virtual objects with success rates significantly better than the chance of guessing it correctly (63.9 ± 11.5%, chance = 16.7%, p < 0.001). We demonstrate that the platform can reliably convey interpretable information about the physical characteristics of virtual objects without the use of hand-mounted devices that would restrict finger mobility. Thus, by offering an immersive virtual experience, xTouch may facilitate a greater sense of belonging in virtual worlds.